Explanation:
Written explanation:
You bring the y to the left side so it "matches" up with the bottom equation. Then you multiply -1 to the bottom or top (preferably the top) and add both equations. Then you solve like you normally would.
Visual explanation:
![5x-y=6\\5x+2y=3\\\\-5x+y=-6\\5x+2y=3\\\\3y=9\\\\y=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ovnzzyq7r98ax0xrwxc5b6f1525xkddb8q.png)
And then, you substitute y into one of the equations, find x, and wala! There might be more steps if you read the directions, but I am just explaining the actual part.
I hope that helps! If you have more questions (like Why did you do that? Where did you get that from?), don't hesitate to ask in the comments below. :)